Correlation of Oral Health Status with Chronic Obstructive Pulmonary Disease in a Tertiary Care Hospital - Nandita Shenoy; Alisha Ono Idris; Vishak Acharya; Junaid Ahmed; Ashok Shenoy; Suchitra Shenoy (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Oral health is considered to be an important factor in respiratory diseases like Pneumonia and chronic obstructive pulmonary disease (COPD). Poor oral health and abusive habits like smoking have been implicated as an independent risk factor for the development of COPD, but few studies have evaluated the association between oral health and COPD.Aim: To assess the oral health and habits of COPD individuals visiting our OPD for their regular checkups. Subjects and Methods: We performed a case-control study of oral health among patients with COPD exacerbators and healthy non COPD controls. Cases had experienced ≥1 exacerbation in the previous 12 months, while controls were healthy patients reporting to the dental OPD for a regular dental checkup. We evaluated oral health status, recorded dental symptoms/habits, and Pulmonary Function Test (PFT). In a subset, we performed blinded dental exams to measure bleeding on probing, probing depth, clinical attachment loss, periodontitis severity, plaque index, gingival index, and carries risk. We evaluated associations between oral health and COPD using logistic regression. Result: Self-reported oral health status and objective dental findings had variations between cases and controls. Participants with COPD had multiple missing teeth, a higher amount of plaque, and calculus indicating poor dental health. Oral candidiasis, keratotic white lesions, and oral melanosis were also present. Conclusion: In the present observational study, we found that participants with COPD have poor oral health that compromised their quality of life probably precipitating an acute exacerbation. The incidence of COPD can be reduced by good oral hygiene measures and preventive oral care.